Nonlinear physics with Mathematica for scientists and engineers - Enns, Richard H (Birkhäuser, 2015)
I. Theory -- 1. Introduction -- 2. Nonlinear Systems. Part I -- 3. Nonlinear Systems. Part II -- 4. Topological Analysis -- 5. Analytic Methods -- 6. Numerical Approach -- 7. Limit Cycles -- 8. Forced Oscillators -- 9. Nonlinear Maps -- 10. Nonlinear PDE Phenomena -- 11. Numerical Simulation -- 12. Inverse Scattering Method -- II. Experimental Activities -- Introduction to Nonlinear Experiments -- 1. Magnetic Force -- 2. Magnetic Tower -- 3. Spin Toy Pendulum -- 4. Driven Eardrum -- 5. Nonlinear Damping -- 6. Anharmonic Potential -- 7. Iron Core Inductor -- 8. Nonlinear LRC Circuit -- 9. Tunnel Diode Negative Resistance Curve -- 10. Tunnel Diode Self-Excited Oscillator -- 11. Forced Duffing Equation -- 12. Focal Point Instability -- 13. Compound Pendulum -- 14. Damped Simple Pendulum -- 15. Stable Limit Cycle -- 16. Van der Pol Limit Cycle -- 17. Relaxation Oscillations: Neon Bulb -- 18. Relaxation Oscillations: Drinking Bird -- 19. Relaxation Oscillations: Tunnel Diode -- 20. Hard Spring -- 21. Nonlinear Resonance Curve: Mechanical -- 22. Nonlinear Resonance Curve: Electrical -- 23. Nonlinear Resonance Curve: Magnetic -- 24. Subharmonic Response: Period Doubling -- 25. Diode: Period Doubling -- 26. Five-Well Magnetic Potential -- 27. Power Spectrum -- 28. Entrainment and Quasiperiodicity -- 29. Quasiperiodicity -- 30. Chua's Butterfly -- 31. Route to Chaos -- 32. Driven Spin Toy -- 33. Mapping.